Antimicrobial resistance pattern of Salmonella spp. isolated from poultry farms in Abakaliki, Nigeria - EMMANUEL NNABUIKE UGBO; MUSTOFA HELMI EFFENDI; ADIANA MUTAMSARI WITANINGRUM; WIWIEK TYASNINGSIH; BERNARD NNABUIFE AGUMAH; AGATHA IFUNANYA UGBO; CHARITY CHINYERE NNABUGWU; DIVINEGIFT OLUCHI OKATA-NWALI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ugbo EN, Effendi MH, Witaningrum AM, Tyasningsih W, Agumah BN, Ugbo AI, Nnabugwu CC, Okata-Nwali DO. 2023. Antimicrobial resistance pattern of Salmonella spp. isolated from poultry farms in Abakaliki, Nigeria. Biodiversitas 24: 5207-5214. Salmonella is a zoonotic foodborne pathogen that can cause serious illness in humans and animals worldwide. Antimicrobial resistance caused by microorganisms has greatly challenged veterinary and human medicine regarding disease treatments. The objective of this study was to evaluate the antimicrobial resistance pattern of Salmonella spp. isolated from poultry farms in Abakaliki, Nigeria. One hundred eighty samples (90 broiler feces; 90 broiler cloacal swabs) were collected from three (3) poultry farms in the Abakaliki metropolis. Samples were analyzed and identified for the presence of Salmonella isolates using standard microbiological and biochemical analysis. The antimicrobial sensitivity test of Salmonella isolates against the selected antibiotics was done using the Kirby-Bauer disk diffusion method on Mueller Hinton agar. The results showed 61 samples (33.9 %) were positive for Salmonella. Feces and cloacal swab samples positive for Salmonella were 46.7% and 21.1%, respectively. Multidrug resistance Salmonella (MDR) strains had an overall prevalence of samples (16.2%), i.e., 7 samples of broiler feces had 7 (16.7%) and 3 samples of cloacal swab (15.8%). Thus, all the MDR Salmonella isolates were 100% resistant to tetracycline and ampicillin. The multiple antibiotic-resistant indexes of the MDR were 0.51. This study indicated that broilers chicken and their products were potential sources of human salmonellosis and sources for transmitting MDR Salmonella in Abakaliki, Nigeria. Poultry farmers should use antibiotics in appropriate dosages in their poultry farms.